Kinematic analysis of ring-shape leap after stepped up the legs and backward balance in artistic gymnastics - Cheng, L.; Li, X.; Zhou, J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Through three-dimensional video analysis and comparative analysis, a study on two artistic gymnastics skills has been done. Results revealed the kinematic characteristics of these two movements. The findings provided useful reference information to coaches for improving the efficiency of scientific training.